Bidirectional Effect of IFN-γ on Th17 Responses in Experimental Autoimmune Uveitis - Shao, Hui; Kaplan, Henry J.; Sun, Deming (Frontiers in Ophthalmology, 2022)
Pro- and ant-inflammatory effects of IFN-γ have been repeatedly found in various immune responses, including cancer and autoimmune diseases. In a previous study we showed that the timing of treatment determines the effect of adenosine-based immunotherapy. In this study we examined the role of IFN-γ in pathogenic Th17 responses in experimental autoimmune uveitis (EAU). We observed that IFN-γ has a bidirectional effect on Th17 responses, when tested both in vitro and in vivo. Anti-IFN-γ antibody inhibits Th17 responses when applied in the initial phase of the immune response; however, it enhances the Th17 response if administered in a later phase of EAU. In the current study we showed that IFN-γ is an important immunomodulatory molecule in γδ T cell activation, as well as in Th17 responses. These results should advance our understanding of the regulation of Th17 responses in autoimmunity.